The History of the Late Warre in Ireland: Richard Bellings and the Religio-politics of the Old English in Later Stuart Ireland - Makino, Sho (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
This thesis investigates how Richard Bellings, a gentleman of the Pale Old English, remembered and reinterpreted the civil wars during the Restoration, focusing on the ways in which the political climate of the 1660s shaped religio-political thinking through his memory-making works. It examines Bellings' The History of the Late Warre in Ireland, a historical account of the 1640s civil wars to demonstrate how Bellings provides a rich case study for examining the political thinking of the landowning class laity regarding government and religion in the context of the Restoration. By situating Bellings within contemporary memory-making controversy, the thesis clarifies his contribution to debates in Restoration Irish politics and Catholic reformation. This thesis intervenes in three areas of historiography. First, despite the acknowledged significance of Bellings' History as a historical document, no systematic study has yet been conducted on either Bellings' biography or his History. Without the thorough study of Bellings' History, historians miss an insight into the Restoration Old English political and religious thinking. Second, while there have been some studies of Catholic and Protestant memory-making of the 1640s, scholars have not yet presented an overview to define the character of these debates or to explore their interrelations. A reassessment of memory-making across the decades in the late Stuart reign is therefore timely. Third, the relationship between the Restoration politics and political debates remain underexplored. This thesis shows that Bellings' History must be read above all in the context of the 1660s, when the land settlement decisively shaped Irish politics, rather than the 1670s as has often been assumed. Within this context, The History served two purposes, both directly connected to the Acts of settlements in 1662 and 1665. Firstly, Bellings sought to counter New English writers who sought to consolidate their political influence through lands acquired during the 1650s. Bellings vindicated his patrons' conduct in the 1641 rebellion and distinguishing loyalist Catholics from rebellious multitudes. Secondly, he responded to the Catholic public discourse that appeared following the Act of Explanation in 1665, defending the reputation and political standing of loyalist Catholics, especially his patron James Butler, duke of Ormond. This thesis also examines Bellings' religious thinking in the wider contexts of diplomacy and ecclesiastical politics. His diplomatic missions in the 1640s and 1650s reveal his pragmatic religio-political outlook that shifted between accepting de facto toleration and seeking royal recognition of Catholicism while already reflecting Gallican tendencies. His role in drafting The Loyal Formulary of the Irish Remonstrance further confirms this orientation. In this light, the later sections of The History emerge not only as a record of Confederate politics but as a Gallican orientation that helped shape loyalist Catholic political thinking across the seventeenth century.
APPROVED
Keywords: Restoration politics; Catholic Confederation; Seventeenth-century Ireland; The Old English; Richard Bellings; Memory politics; Cultural history; Catholic reformation; Catholic loyalism; Exile; Land settlement